2015
DOI: 10.4103/1450-1147.153908
|View full text |Cite
|
Sign up to set email alerts
|

Radiosynovectomy of Painful Synovitis of Knee Joints Due to Rheumatoid Arthritis by Intra-Articular Administration of 177 Lu-Labeled Hydroxyapatite Particulates: First Human Study and Initial Indian Experience

Abstract: The aim of this study is to assess the effectiveness of Radiosynovectomy (RSV) using 177Lu-labeled hydroxyapatite (177Lu-HA) in the treatment of painful synovitis and recurrent joint effusion of knee joints in rheumatoid arthritis (RA). Ten patients, diagnosed with RA and suffering from chronic painful resistant synovitis of the knee joints were referred for RSV. The joints were treated with 333 ± 46 MBq of 177Lu-HA particles administered intra-articularly. Monitoring of activity distribution was performed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
2
9
0
Order By: Relevance
“…The first case report was described by Kamaleshwaran et al, in which 90 Y‐HA was injected at knee joint for treatment of villonodular synovitis (PVNS) 155 . Further, Shinto et al used 177 Lu‐labelled HA for treatment of chronic synovitis and rheumatoid arthritis 156 . HA‐conjugated 153 Sm was used for the treatment of knee synovectomy in haemophilia patients 157 .…”
Section: Different Nanoparticle Systems Used For Delivery Of Radiophamentioning
confidence: 99%
“…The first case report was described by Kamaleshwaran et al, in which 90 Y‐HA was injected at knee joint for treatment of villonodular synovitis (PVNS) 155 . Further, Shinto et al used 177 Lu‐labelled HA for treatment of chronic synovitis and rheumatoid arthritis 156 . HA‐conjugated 153 Sm was used for the treatment of knee synovectomy in haemophilia patients 157 .…”
Section: Different Nanoparticle Systems Used For Delivery Of Radiophamentioning
confidence: 99%
“…Radioactive decay transfers radiant energy to the synovial tissue, which gradually causes fibrosis of the synovial tissue, thereby reducing blood perfusion and effusion of inflammatory joints to reduce the infiltration of inflammatory cells (Ahmad and Nisar, 2018 ). Given that the nuclides used to treat arthritis are mostly short-range beta radiation (within a distance of 10 mm), the radiation exposure outside the joint is very low (Kamaleshwaran et al, 2015 ; Shinto et al, 2015 ). Studies have demonstrated that RSV has a relief effect in 60–80% of RA patients (Karavida and Notopoulos, 2010 ).…”
Section: Radiation-based Energy-conversion Nanotherapy For Ra Treatmementioning
confidence: 99%
“…First human study and initial Indian experience in the treatment of painful synovitis and recurrent joint effusion of knee joints in rheumatoid arthritis using 177 Lu-labeled HA was reported by Shinto and coworkers. 86 Formerly, preparation and preliminary biological evaluation of 177 Lu-labeled HA as a promising agent for radiation synovectomy of small joints was described by Chakraborty and co-workers. 87 The use of 153 Sm-HA for knee synovectomy in hemophilia was reported by Calegaro et al 88,89 Effectiveness of radiation synovectomy with 90 Y and 153 Sm particulate hydroxyapatite in rheumatoid arthritis patients with knee synovitis was reported by dos Santos and co-workers.…”
Section: D Nanocarriersmentioning
confidence: 99%
“…For example, McDevittand co-workers 194 synthesized 86 Y-CNT construct from amine-functionalized, water-soluble CNT by covalently attaching multiple copies of DOTA chelates and then radiolabeled with the positron-emitting metal-ion, yttrium-86. The whole-body distribution and clearance of 86 Y were characterized at 3 and 24 h postinjection using PET. The yttrium-86 cleared the blood within 3 h and distributed predominantly to the kidneys, liver, spleen, and bone.…”
Section: Nanotubesmentioning
confidence: 99%
See 1 more Smart Citation